Sanitation of State Elementary School 008 Leleng, Sekolaq Darat District In 2022 - Rahmatullah, Ilham; Apriyani, Apriyani; Eris, Anastasia (Sean Institute, 2023)
Sanitation is part of environmental health science, which includes the ways and efforts of individuals or communities to control and control the external environment that is harmful to health and which can threaten human survival. Analyse clean water supply facilities, bathroom/wc sanitation facilities, and wastewater treatment facilities at Leleng Elementary School, Sekolaq Darat District. Qualitative research methods using a phenomenological approach The research subjects in this scientific paper consist of 1 main informant, 2 key informants, and 2 supporting informants. Results: Sanitation at SDN 008 Leleng, Sekolaq Garat Subdistrict, in the water supply facilities, still uses water transporters using a conductor, the school latrine sanitation facilities are classified as not meeting the standards, and wastewater sewers are found to not meet the requirements. Conclusion: The need to use clean water storage facilities and provide adequate lighting, such as installing lights on school latrines, can improve the quality of school sanitation at SDN 008 Leleng, Sekolaq District.